The City in Words across Time: A Corpus-Based Literary Approach Using Istanbul as a Case Study - Asmaa Ramil (Skad)
This paper examines how a combination of qualitative literary analysis and corpus methods (mainly, collocation analysis) can shed light on the changing representations of a city across different temporal and cultural contexts. Using Istanbul as a case study, it examines the portrayal of the city in three literary works spanning more than a century: Pierre Loti’s Aziyadé (1879), Ahmet Hamdi Tanpınar’s The Time Regulation Institute (1961) and Orhan Pamuk’s Istanbul: Memories and the City (2003). The study explores how each author portrays the city through a distinct lens – Loti’s Orientalist gaze, Tanpınar’s modernist reflection, and Pamuk’s postmodern engagement. It highlights how macro literary narratives and micro linguistic patterns (mainly, on the word level) interact to construct images of the city, reflecting socio-political dynamics and demonstrating the interplay among tradition, memory and change in shaping Istanbul’s individual and collective cultural identities from the late 19th century to the early beginnings of the 21st. The paper considers the tensions between the past, the present and the in-between, highlighting how literature interacts with these tensions to construct and deconstruct the image of Istanbul across time. While the focus is on Istanbul, the methods and insights offered here provide a flexible framework for analysing representations of other cities.